If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -3 = 1 Reorder the terms: -3 + 2p = 1 Solving -3 + 2p = 1 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2p = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 2p = 1 + 3 2p = 1 + 3 Combine like terms: 1 + 3 = 4 2p = 4 Divide each side by '2'. p = 2 Simplifying p = 2
| 40+5L=200 | | (8x+17y)+(11x-8y)= | | 20+4L=50 | | -100x^4+30x^3+40x^2+50x+40=0 | | (b*b)+3+2(b*b)+4-7= | | -16t^2+105t=63.2 | | a+36=120 | | -9y^2=-144 | | W^2-10w=250 | | x-3.4=9.24 | | 3(2x-9)=x+44 | | F(X+1)=2(X+16) | | 3m-6+(m*m)-5m+1= | | 2x-3y=7.25 | | y+1.4=9.52 | | 3+ln(8x)=18-2ln(x) | | 5x+4y-3=0 | | 2-9x=65 | | x^2+6x+62=4 | | -78=-6(v+5) | | (2x-1)y=21 | | 2x+3y=7.25 | | lnx=44 | | 2x+3-4+3-4x=8-3 | | 3/5x?=21 | | 6-2x^2=42 | | -11(-5k-11)+5(-11k+1)=-6k-k | | -12=3-5w | | 3m-6+(m)(m)-5m+1= | | b^2-4b+12=-6 | | b/.5=9/2.5 | | 5x+20=3+66 |